OPTIMIZING POSTOPERATIVE ANALGESIA: A RANDOMIZED COMPARISON OF INTRAVENOUS IBUPROFEN AND PARACETAMOL IN ABDOMINAL STOMA CLOSURE - Dr. Bharani kumar B; Dr. Rama Wason; Dr. Dishank Rawat; Dr. Amodini Kukreja; Dr. Rohan Khandelwal; Dr. Sakshi Khandelwal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Postoperative pain is a common challenge following abdominal stoma closure surgeries. This study aimed to compare the analgesic efficacy of intravenous (IV) ibuprofen with IV paracetamol in adult patients undergoing these surgeries under subarachnoid block. Materials and Methods: A total of 132 patients were randomly allocated into two groups: Group I (n=66) received IV ibuprofen (20mg/kg) every 6 hours, and Group P (n=66) received IV paracetamol (15mg/kg) every 6 hours. Data collected included age, gender, anthropometric parameters, duration of surgery, Visual Analog Scale (VAS) scores at rest and during movement at various time intervals (0, 1, 2, 6, 12, 18, 24 hours), and any adverse effects. Rescue analgesia (IV tramadol 1mg/kg) was administered if the VAS score exceeded 40mm. Results: Postoperative VAS scores at rest showed no statistically significant difference between the two groups throughout the observed intervals. For VAS scores on movement, Group I showed significantly lower scores at 0 hours and 6 hours compared to Group P (p=0.019 and p=0.016, respectively), though this difference was not considered clinically significant. While 21 patients in Group I and 34 patients in Group P required rescue tramadol, indicating a statistically significant difference in the incidence of rescue analgesia (p=0.022), the mean dosage of tramadol consumed was also statistically significantly lower in Group I (24.2 ± 37.2 mg) compared to Group P (39.4 ± 41.4 mg) (p=0.029). Adverse effects were observed in 11 patients (16.7%) in Group I and 4 patients (6%) in Group P, with no statistically significant difference between groups. Conclusions: The analgesic efficacy of IV ibuprofen was found to be equivalent to IV paracetamol in terms of VAS scores but demonstrated a statistically significant reduction in the incidence and mean dosage of rescue analgesia compared to IV paracetamol in adult patients undergoing abdominal stoma closure surgeries under subarachnoid block. Both agents showed comparable adverse effects. These findings suggest a potential advantage of IV ibuprofen in reducing opioid requirements.